EFFECT OF PRACTICAL ACTIVITIES ON ACADEMIC ACHIEVEMENT OF SENIOR SECONDARY SCHOOL STUDENTS IN BIOLOGY IN OYE LOCAL GOVERNMENT AREA, EKITI STATE (UNIZIK Journal of STM Education, 2024)
This study investigates the effect of practical activities on the academic performance of senior secondary school biology students in Oye Local Government Area, Ekiti State. The study adopted the quasi-experimental pre-test and post-test research design. The population of the study comprised all the 1,455 biology students in public senior secondary schools in Oye Local Government Area, Ekiti State.The purposive sampling technique was employed to 2select two (2) schools in Oye local government area. A sample of 50 students with 25 each for the two groups was selected purposefully. Biology Performance Test (BPT) was used to collect data for the study.The instrument was subjected to face and content validity by the researcher's supervisor and experts in the field of biology education. The test-retest method was used to determine the reliability of the instrument and a reliability coefficient of 0.84 was computed using Pearson Product Moment Correlation. The data was analyzed using descriptive and inferential statistics. The descriptive statistics of frequency counts, percentages, mean and standard deviation were used to answer the research questions, while the inferential statistics involving t-test analysis, was used to test the hypotheses. All the hypotheses were tested at a 0.05 level of significance.The study revealed that there is a significant difference in the performance mean scores of male students taught using intensive practical strategy compared to their counterparts taught using conventional teaching strategy. The difference favours the male students in the experimental group having a higher performance means score than their counterparts in the control group. Also, there is a significant difference in the performance mean scores of female students taught using intensive practical strategy compared to their counterparts taught using conventional teaching strategy. The difference favours the female students in the experimental group, having a higher performance means score than their counterparts in the control group. Based on the findings, it was recommended among others, that government and school administrator should encourage teachers to engage in professional developments that would ensure the use of intensive practical strategy in schools. Also, teacher should carry both gender (male and female) along during practical class so that both genders would develop the intensive practical strategy. Teachers should adopt intensive practical strategy for biology and other science instruction in secondary school.
Keywords: Biology, Gender, Laboratory, Practical activities, Academic Performance